Somatotype of patients with type 2 diabetes in a university hospital in Mexico - Urrutia García, Krystle; Martínez Cervantes, Tomás Javier; Salas Fraire, Oscar; Guevara Neri, N. P. (UANL. Facultad de Medicina, 2015)
The aim of the study was to determine the somatotype of Mexican type 2 diabetes patients, using the Heath and Carter somatotype method. Methods: The study was conducted on 180 subjects, who underwent an anthropometry following the restricted format established by the International Society for the Advancement of Kinanthropometry (ISAK). A database was elaborated and we obtained descriptive measures such as age, weight, height and the 3 somatotype components. Results: The average age was 58 years (±11 SD); 58.6 years (±10.9 SD) for males and 56.8 years (±11 SD) for females. The average weight was 77.5 kg (±16.7); 80.7 kg (±14.6 SD) for males and 75 kg (±17.8 SD) for females. The results indicate that the mean somatotype for Mexican type 2 diabetes patients was 6.3, 6.4, 0.6. Diabetic females have higher mean values for endomorphy (7.3) and mesomorphy (6.7) and lower mean values for ectomorphy (0.4) than their male counterparts (5.0, 6.0 and 0.8, respectively). It is evident that endomorphy is predominantly in females, in contrast to males, since there are known differences in fat and muscular mass between both genders. Conclusions: The results are similar to previous studies presented for other diabetic populations. Sex differences are significant and especially higher for the endomorphic component, with generally higher values in females. It is important to continue this research direction with bigger samples and the study of other risk factors that directly affect the somatotype of type 2 diabetes.